FORAGE YIELD RESPONSE OF SOME GRASS PEA GENOTYPES TO ORGANIC FERTILIZER AND STUBBLE HEIGHT IN DIFFERENT ENVIRONMENTAL CONDITIONS OF SULAIMANI REGION- IRAQ - Hevy Latif Saeed; Sanarya Rafiq Muhammed (The Iraqi Journal of Agricultural science, 2025)
This study was conducted at two locations, Qlyasan Agricultural Research Station and Kanipanka Nursery Station, during the 2023–2024 winter season to investigate the effects of organic fertilizer and stubble height on forage yield attributes of grass pea genotypes. A split-split plot design was used with three factors: fertilizer application (F0= no fertilizer, F1= organic fertilizer), genotypes (G1: Local, G2: IGC-2011-62, G3: IGC-2011-35, G4: IGC-2011-9), and stubble height (SH1= 5cm, SH2 = 10cm). Fertilizer application significantly increased DFY in Kanipanka. Genotype significantly influenced most forage yield attributes, with G1 showing the highest values. Stubble height significantly affected GFY and DFY, particularly in Qlyasan. Kanipanka outperformed Qlyasan in key yield attributes. Cluster analysis identified two genotype groups, indicating genetic variability. Proper management of fertilizer. Interaction effects were observed for fertilizer × genotype and fertilizer × stubble height. Genotype selection and stubble height can optimize forage yield.